Study on melt jet breakup behavior with nonorthogonal central-moment MRT color-gradient lattice Boltzmann method. (June 2021) - Cheng, Hui; Zhao, Jiyun; Saito, Shimpei; Cheng, Songbai
Abstract: In this paper, the melt jet breakup behavior are numerically studied in 3D with nonorthogonal central-moment MRT color-gradient lattice Boltzmann method, which could significantly enhance the numerical stability and accuracy when applied to flows with very high Reynolds number. Firstly, the methodology to simulate immiscible two-phase flow is validated by conducting droplet oscillation tests. Then the ability of this model to accurately predict melt jet breakup in water is validated by simulating molten Wood's metal jet breakup experiments. Meanwhile, the breakup mechanisms are clarified. For the leading edge, the breakup of the side part is due to large eddies, the main part of the leading edge starts breakup owning to Rayleigh-Taylor instability. For the jet column, small droplets and filaments are stripping due to Kelvin-Helmholtz instability, segment breakup of the jet column is owning to Rayleigh-Taylor instability. Finally, the model is employed to simulate molten corium jet breakup in water. The hydrodynamic characteristics such as jet penetration depth, jet breakup length and fragment size are analyzed in detail. It is found that the simulation results are basically consistent with the dimensionless jet breakup length predicted by Epstein et al.'s correlation when E 0 = 0.1, but relatively shorter. RTI theory significantly overestimates mass median diameter while critical Weber number and KHI theories underestimate it.